Treatment Tactics after Relapses in Cases of Complex Treatment of Cervical Cancer (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
For patients with primary stage ⅣB, persistent, or recurrent cervical cancer, chemotherapy remains the standard treatment, although it is neither curative nor associated with long-term disease control. In this review, we summarized the history of treatment of recurrent cervical cancer, and the current recommendation for chemotherapy and molecular targeted therapy.This article is devoted to the tactics of treatment of cervical cancer (BBS) in cases of recurrence after complex treatment. In cases of relapse, it is important to determine and use effective treatment methods. The article examines methods for detecting relapses, what treatment strategies are used for relapses at what stage, and new treatment technologies.